Mitochondrial Impairment by MitoBloCK-6 Inhibits Liver Cancer Cell Proliferation - Kabiri, Yaschar; Fuhrmann, Anna; Becker, Anna; Jedermann, Luisa; Eberhagen, Carola; König, Ann-Christine; Silva, Tiago Barros; Borges, Fernanda; Hauck, Stefanie M.; Michalke, Bernhard; Knolle, Percy; Zischka, Hans (Frontiers in Cell and Developmental Biology, 2021)
Augmenter of liver regeneration (ALR) is a critical multi-isoform protein with its longer isoform, located in the mitochondrial intermembrane space, being part of the mitochondrial disulfide relay system (DRS). Upregulation of ALR was observed in multiple forms of cancer, among them hepatocellular carcinoma (HCC). To shed light into the ALR role in the DRS in HCC, we pharmacologically inhibited ALR, resulting in profound mitochondrial impairment and cancer cell proliferation deficits. These effects were mostly reversed by supplementation with bioavailable hemin b, linking DRS, and specifically ALR function, to mitochondrial iron homeostasis. Since many tumor cells are known for their increased iron demand and since increased iron levels in cancer are associated with poor clinical outcome, these results help to further advance the intricate relation between iron and mitochondrial homeostasis in liver cancer.